(untitled) (Malay Literature, 2012)
Among specimens of traditional Malay literary polemics, or rather, "wars of books", we find an interesting group of texts of the mid or late seventeenth century, which narrate how an Acehnese embassy was dispatched to Ottoman Turkey to obtain "large cannons". Remarkably, alongside literary pieces composed in Aceh, this group also includes the Turkish episode of Hikayat Hang Tuah (HHT), the epic created in Johor which describes the epoch of the Malaccan sultanate. However, HHT is a double-layered work in which Malacca not infrequently stands for Johor, whose relations with Aceh were more often than not hostile. HHT’s author covertly polemicizes against Acehnese literary works, striving to prove that Malacca (read Johor) allegedly established diplomatic relations with the Ottomans earlier than Aceh. HHT also attempts to show that its mission to Istanbul was much more successful than Aceh’s and that it completed the recognition of Malacca/Johor across the entire political space from China to Turkey. Yet, the political and literary agendas of HHT’s author differ radically. In the former, the forces of repulsion hold sway, which leads HHT to depict the triumph of Johor in its rivalry with Aceh. In the latter, on the contrary, the forces of attraction dominate. For this reason the Turkish episode in HHT borrows the plot of Acehnese works, constructs its portrayals of Istanbul from a mosaic of Acehnese sources, and resorts to the grand Acehnese literary style of the "gold-and-jewel" variety. Keywords: traditional Malay literature, Hikayat Hang Tuah, Malacca, Johor, Aceh, Turkey, Istanbul, the Ottomans, Acehnese embassy, political agenda, palimpsest, war of books, gold-and-jewel style